FACTORS INFLUENCING EMPLOYEES TO COMMIT FRAUD IN WORKPLACE EMPIRICAL STUDY IN INDONESIAN HOSPITALS - Aditya Pandu Wicaksono; Dekar Urumsah (Asia Pacific Fraud Journal, 2016)
Fraud is a part of unethical behavior, which occurs around the world. It occurs because of some factors. This study aims to analyze the factors influencing fraud intention. This research use survey method by distribute questionnaire to respondent with convenience sampling to collect data. The questionnaires fill completely by 154 non-medical employees in some hospitals in Yogyakarta, Indonesia. Smart PLS 2.0 is used to analyze the statistics. The result of the study indicates that organizational commitment and morality leadership have positive effect against fraud intention. Meanwhile, love of money, morality leadership, work environment, religious faith, and organizational culture has negative effect against fraud intention. This research provides the influence of financial and non-financial factors to fraud intention and results can be guideline to protect organization from unethical act.